Banni Pooja (Shami Vriksha Pooja) and its Significance for Mysore Dasara Festival - SUMA V.; RAVIKUMAR (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2024)
In this paper an attempt has been made to explain the worship of Shammi Tree (Banni Mara) on the Vijaya-Dasami day in Mysore. Vijayadashami is celebrated differently in different parts of India, but one noticeable thing in most of these celebrations is the importance given to certain plants. Banni tree or Shammi tree is very sacred to Hindus and comes into prominence during Dasara festival. Every Hindu warrior before going to war would offer prayers to Banni tree and then proceed. Banni tree holds a special place in the Mysore Dasara where it’s worshipped on the Vijay-Dashami day. While every region has its own unique flavor and significance for the day, this is a piece discussing a ritualistic practice – Worship of Shammi Vruksha (Banni Tree) and giving Shammi Patra (Banni ele in Kannada) to others. Not only this, but there are also so many things were discussed in this paper.